Sono-bromination of aromatic compounds based on the ultrasonic advanced oxidation processes - Fujita, M. (Elsevier B.V., 2015)
A novel, mild "sono-halogenation" of various aromatic compounds with potassium halide was investigated under ultrasound in a biphasic carbon tetrachloride/water medium. The feasibility study was first undertaken with the potassium bromide and then extended to chloride and iodide analogues. This methodology could be considered as a new expansion of the ultrasonic advanced oxidation processes (UAOPs) into a synthetic aspect as the developed methodology is linked to the sonolytic disappearance of carbon tetrachloride. Advantages of the present method are not only that the manipulation of the bromination is simple and green, but also that the halogenating agents used are readily available, inexpensive, and easy-handling. Â© 2015 Elsevier B.V. All rights reserved.